Relation between the Social Status of Pupils and Their Professional Aspirations - Iljina, Olga; Purvaneckienė, Giedrė (Acta Paedagogica Vilnensia, 2012)
The paper reports on the influence of the social status of 12th grade pupils on their professional aspirations. The concept of the social status of a pupil is being discussed and for the empirical research purposes is defined as his (her) family social status. The paper explores the results of a pilot survey of 12th grade pupils in three schools of different type: gymnasium, comprehensive, and vocational. Parent’s educational level and their earnings were used as the indicators of family social status. It appears that social status of pupils in three types of schools differs: pupils from the highest social status families are related to the gymnasium, from the middle social status – to comprehensive school, and from the lowest – to vocational school. It proves that the crucial decision on the professional perspectives of pupils is being taken after the 8th or 10th grade when the type of school is selected. In the survey, a statistically significant correlation between achievements of pupils, their professional choices and aspirations and the type of school as well parent’s educational level and earnings has been found. This raises the issue of equal opportunities for pupils from different social status families in the Lithuanian education system.